Anxiety and Competence Achievement of Midwifery students During Midwifery Clinical Practice of Maternal Neonatal Emergency - Anis Kusumawati; Titi Savitri Prihatiningsih; Yayi Suryo Prabandari (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2017)
Background: Anxiety is often experienced by students when following clinical education. Anxiety at moderate level is required for the learning process, but at high level it lowers the learning. The objective is to determine the level of anxiety, competency achievement, the relationship between them and the things that are perceived by the students and the clinical instructors when following clinical practice.Methods: A quantitative, cross sectional study using questionnaires to 42 midwifery students continued with the qualitative by in-depth interviews with three students and six clinical instructors.Results: The level of anxiety was no to mild anxiety by 19.05%, mild to moderate anxiety by 66.67%, and moderate to severe anxiety by 14.28%. Around 2.38% of the students earned a grade of a B, 45.24% earned a B + and 52.38% earned an A. The relationship between the level of anxiety and competency achievement was shown with an r value of -0.043.Conclusion: The level of anxiety in clinical practice of midwifery students was mild to moderate, and the competency achievement was excelent. There was a negative and very weak correlation between the level of anxiety and competency achievement. Things perceived by the student following clinical practice were a matter of personalization, innovation, individualization, involvement, task orientation, and satisfaction, while things perceived by the clinical instructors were a matter of time constraints, much work load, student preparedness, student ability level, challenge to patient, student motivation, and hospital environments.